Weaving of Aspects in Business Process Management - Amin Jalali (Complex Systems Informatics and Modeling Quarterly)
Separation of cross-cutting concerns is an important issue in business process management, where Aspect-Oriented Business Process Modeling (AO-BPM) aims to support this separation through a new form of encapsulation technique. Although different researchers have investigated how these models can be designed to support separation of non-retroactive cross-cutting concerns, there is no study that defines the separation of retroactive ones. The lack of a unified definition of the syntax and the operational semantics for these models hinders their enactment in practice as well. As a result, the perceived usefulness and usability of these approaches have not yet been investigated so far. Thus, this article fills this gap by formalizing an AO-BPM language and the semantics that can support enactment of such models. The semantics is validated through the state-space analysis technique, and the feasibility of the implementation is also demonstrated. The perceived usefulness and easy to use of the AO-BPM is evaluated by applying the Technology Acceptance Model during a workshop session. The result shows that participants perceived the approach usable and easy to use.